Willingness to pay for digital wellbeing features on social network sites: a study with Arab and European samples - Alshakhsi, Sameha; Babiker, Areej; Sindermann, Cornelia; Al-Thani, Dena; Montag, Christian; Ali, Raian (Frontiers in Computer Science, 2024)
In recent years, concerns over the potential negative impacts of social network sites (SNS) on users’ digital wellbeing are on the rise. These concerns have sparked a growing demand for SNS to introduce changes to their business model and offer features that prioritize users’ well-being, even if it means introducing fees to users. Still, it is questionable whether such a new model is welcomed by users and commercially valid. In this paper, we investigate i) people’s willingness to pay (WTP) for digital wellbeing services designed to foster more autonomy, control, and personal growth in users and ii) the influence of sociodemographic variables, personality, and social networks use disorder (SNUD) on WTP. Data were collected through an online survey with participants from two distinct cultural contexts, the European and Arabic. The samples comprised 262 participants from Europe (Males: 57.63%) and 251 from Arab countries (Males: 60.56%). The participants ranged in age from 18 to 66 years (MEurope = 29.16, SD = 8.42; MArab = 31.24, SD = 8.23). The results revealed that a notable proportion of participants were willing to pay for digital wellbeing services (Europe = 24 %; Arab: 30%). Females in the European sample demonstrated a higher WTP for “Mental Health Issues Minimization” compared to males. In the Arab sample, males showed a higher WTP for “Safeguarding Data Privacy” than females. Multiple regression analyses revealed that SNUD and the need for cognition emerged as significant and positive predictors of WTP in both the European and Arab samples. Differences in the relations of personality traits and sociodemographic variables on WTP in each sample were noted. These insights contribute to our understanding of the factors shaping individuals’ preferences and valuation related to digital wellbeing services on social media and highlight the importance of considering sociodemographic variables and personal factors as well as cultural contexts when planning and introducing them.